Pazopanib in the treatment of renal cell carcinoma. (January 2011) - Cowey, C Lance; Hutson, Thomas E; Figlin, Robert
A variety of novel molecularly targeted drugs have been introduced for the treatment of metastatic renal cell carcinoma (RCC) over the last several years. Pazopanib is the most recent addition and functions as a potent inhibitor of the vascular endothelial growth factor receptor tyrosine kinase. Pazopanib has been studied in two large randomized clinical trials demonstrating the efficacy and tolerability of this drug in RCC. Based on these results, pazopanib has become the sixth targeted agent approved for the treatment of RCC. This review will focus on pazopanib''sin vitro activity, clinical effectiveness, side-effect profile and how it can be integrated among the other available drugs in the management of RCC.